SOLIDARITAS DAN PERDAMAIAN DUNIA DALAM SOLLICITUDO REI SOCIALIS - CB. Mulyatno (Jurnal Teologi (Journal of Theology), 2015)
Encyclical is a form of social teaching of the Pope. The focus of this research is to explore the meaning of solidarity and peace and the relation of both in Solicitudo Rei Socialis. It elaborates a reflective method for analyzing the encyclic. This research comes to a conclusion that solidarity and common good are essential contents of peace. Peace is born in heart of each person and develops in a coexistence life in which every person respects each other. Solidarity is a commitmen and collaboration to develop community marked by dialogal ways. It is the responsibility of each person in the society in actualizing a peacefull world. Solidarity and collaboration in achieving common good is a social face of peace. Therefore, in a context of cold-war, Pope underlines that solidarity is a commitment and responsibility of each person and nation to live and to develop a qualified living-together in collaborative, respectfull and dialogal ways.